Forecasting algae and shellfish carbon sink capability on fractional order accumulation grey model - Haolei Gu; Kedong Yin (Mathematical Biosciences and Engineering, 2022)
Marine biology carbon sinks function is vital pathway to earned carbon neutrality object. Algae and shellfish can capture CO2 from atmosphere reducing CO2 concentration. Therefore, algae and shellfish carbon sink capability investigate and forecast are important problem. The study forecast algae and shellfish carbon sinks capability trend base on 9 China coastal provinces. Fractional order accumulation grey model (FGM) is employed to forecast algae and shellfish carbon sinks capability. The result showed algae and shellfish have huge carbon sinks capability. North coastal provinces algae and shellfish carbon sinks capability trend smoothness. South and east coastal provinces carbon sinks capability trend changed drastically. The research advised coastal provinces defend algae and shellfish population, expand carbon sink capability. Algae and shellfish carbon sink resource will promote environment sustainable develop.